"Forgive but Not Forget": The Behavior of Relationship Banks When Firms Are in Distress. (17th October 2018) - Schäfer, Larissa
Abstract: Do relationship banks help firms in distress? Combining a survey-based measure of relationship lending with unique credit registry data, I examine the effect of relationship lending on loan performance. I find that the same firm in the same time period is more likely to become delinquent on a relationship-based loan relative to a transaction-based loan. Higher delinquencies do not, however, result in more defaults or less loan recoveries for relationship banks when loans mature relative to transactional banks. Conditional on past delinquencies, relationship banks are more likely to offer follow-up financing and extract rents. Consistent with theory, relationship banks tolerate temporarily bad results, yet extract rents and secure future business in return. The paper provides new empirical evidence for rent extraction by relationship banks that have been lenient to distressed firms in the past.